Elevated plasma S100B levels in high altitude hypobaric hypoxia do not correlate with acute mountain sickness. (September 2014) - Winter, Craig D.; Whyte, Timothy R.; Cardinal, John; Rose, Stephen E.; O'Rourke, Peter K.; Kenny, Richard G.
Abstract : Objectives: Ascent to high altitude may result in a hypobaric hypoxic brain injury. The development of acute mountain sickness (AMS) is considered a multifactorial process with hypoxia-induced blood–brain barrier (BBB) dysfunction and resultant vasogenic oedema cited as one potential mechanism. Peripheral S100B is considered a biomarker of BBB dysfunction. This study aims to investigate the S100B release profile secondary to hypoxic brain injury and comment on BBB disturbance and AMS. Methods: A prospective field study of 12 subjects who ascended Mt Fuji (3700 m) was undertaken. Results: The mean baseline plasma S100B level was 0·11 μg/l (95% CI 0·09–0·12), which increased to 0·22 μg/l (95% CI 0·17–0·27) at the average of three high altitude levels (2590, 3700, and 2590 m on descent) (P < 0·001). The mean level for the seven subjects who experienced AMS rose from 0·10 to 0·19 μg/l compared to 0·12 to 0·25 μg/l for the five subjects who did not develop AMS ( P = 0·33). Conclusion: Ascending to 3700 m resulted in elevated plasma S100B levels but this was not associated with AMS.